1968
DOI: 10.1149/1.2411340
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of Adsorption, Surface Reaction, and Electrochemical Oxidation of Propane on Platinum in Hydrofluoric Acid

Abstract: The rate of adsorption of propane on platinum in 37 m/o HF at 30~ has been measured using single linear voltage sweep techniques as a complement to earlier studies at 90~ The surface coverage by hydrocarbon species was measured as a function of adsorption time and potential. The rate of adsorption follows Langmuir kinetics with a third-order dependence on free surface. The rate of reaction of the initial adsorbate at 90~ to form a highly electroactive species (type I) was also measured, and found to be proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1971
1971
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…where the parentheses denote the different adsorbed species. The possibility that the different adsorbed species may be linked through interconversion surface processes can be formally expressed in the following way (C2H2) - Reactions [2a] and [2b] are comprised within the reaction formalism earlier proposed for the surface reactions taking part in the electrooxidation of propane on platinum in 37 mol percent HF at 90~ (24,25). Otherwise, reaction [2c] has been recently postulated to interpret the cathodic hydrogenation of one of the species formed during the electrosorption of methane in 1N H~SO4 at 60~ (22).…”
Section: Discussionmentioning
confidence: 99%
“…where the parentheses denote the different adsorbed species. The possibility that the different adsorbed species may be linked through interconversion surface processes can be formally expressed in the following way (C2H2) - Reactions [2a] and [2b] are comprised within the reaction formalism earlier proposed for the surface reactions taking part in the electrooxidation of propane on platinum in 37 mol percent HF at 90~ (24,25). Otherwise, reaction [2c] has been recently postulated to interpret the cathodic hydrogenation of one of the species formed during the electrosorption of methane in 1N H~SO4 at 60~ (22).…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed [7] that the hydrocarbon is dissociatively chemisorbed to form an adsorbed hydrogen atom and a carbonaceous species that subsequently dehydrogenates forming additional hydrogen atoms and other surface species that ultimately either convert to CO 2 or oligomerize to form a carbonaceous residue on the electrode surface. An alternative mechanism [8] suggested that the rate determining step was the chemical reaction between an adsorbed hydrocarbon (acetylene) and an adsorbed OH species that resulted from water dissociation.…”
Section: Several Other Factors Influence the Performance Ofmentioning
confidence: 99%
“…It is well known that these types of species are readily formed after the electro-oxidation of hydrocarbons on Pt electrodes. 33,42,43 In particular, based on electrochemical measurements, Brummer and Turner 44 suggested that the electro-oxidation of the propane on Pt electrodes followed a parallel scheme, in which the CH species ͑called type II by the authors͒ were not forerunners of the O-type species ͑type I͒ in a scheme C 3 H 8 → O-type → CO 2 . In the case of methanol oxidation, it was found from Fourier transform infrared ͑FTIR͒ measurements that COH is not necessarily formed a step ahead of CO on the route to CO 2 , but rather CO could be formed in a parallel path from a series of steps following the adsorption of methanol.…”
Section: Ionmentioning
confidence: 99%